2016
DOI: 10.22456/1679-9216.80936
|View full text |Cite
|
Sign up to set email alerts
|

Catalase and Glutathione Peroxidase in Dogs Naturally Infected by Leishmania infantum

Abstract: Background: Canine leishmaniasis (CanL) is caused by an obligatory intracellular parasite of Leishmania genus that  affects organs and tissues. Several studies evaluate the role of reactive oxygen species (ROS) in the pathogenesis of many diseases. The overproduction of ROS on infectious diseases can induce an imbalance between oxidants and antioxidants at cellular or systemic level. Thus, the aim of this study was to evaluate the activity of antioxidant enzymes in CanL.Materials, Methods & Results: Female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Similar observations were reported from Serarsalan et al [ 10 ] who observed significantly higher levels of serum malondialdehyde (MDA). ROS overproduction can induce an imbalance between oxidant and antioxidant at the cellular or systemic level, leading to the establishment of oxidative stress [ 33 ]. O 2 − is the precursor of other harmful oxidants such as H 2 O 2 and its derivates [ 11 ], and O 2 − production was significantly elevated during phagocytosis of the stationary phase promastigotes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were reported from Serarsalan et al [ 10 ] who observed significantly higher levels of serum malondialdehyde (MDA). ROS overproduction can induce an imbalance between oxidant and antioxidant at the cellular or systemic level, leading to the establishment of oxidative stress [ 33 ]. O 2 − is the precursor of other harmful oxidants such as H 2 O 2 and its derivates [ 11 ], and O 2 − production was significantly elevated during phagocytosis of the stationary phase promastigotes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) has been demonstrated to be the molecule mostly involved in intracellular killing of Leishmania , both in vitro and in vivo [ 36 ]. In dogs, single and coinfections by L. infantum , E. canis and B. vogeli cause an increase in the levels of NO [ 33 ]. NO becomes increasingly important as a defense mechanism during the intracellular amastigote stage [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPx може бути також використана як біомаркер для діагностики паразитарних захворювань собак. Зокрема встановлене зниження активності цього ензиму в крові тварин інфікованих Leishmania infantum (Lopes-Neto et al, 2016) та Babesia canis canis (Crnogaj et al, 2017). Тому кров для досліджень необхідно брати до анестезії та враховувати загальний стан організму тварин.…”
Section: вступunclassified
“…Using 3.5 mg/kg bw to control T. evansi can be considered as underdose, as is often the case, and thus it can help to cure clinical affection, but most of the time the animals will remain carriers of the parasites (Desquesnes et al., ). Finally, in dog treatment, in order to avoid toxic effects but to increase the drug efficacy, serial treatments using 3.5 mg/kg have been attempted (Howes et al., ). ISMC: If the objective is to cure the animal and get rid of the infection, high doses such as 1–2 mg/kg bw should be used; however, success cannot be ascertained and toxicity may limit such practice. In addition, as a slow eliminated drug, ISMC may easily induce resistance, so it is not a drug of choice for the control of Surra.…”
Section: Assessmentmentioning
confidence: 99%